Preferensi Siswa Sekolah Menengah Atas terhadap Pencarian Informasi Keamanan Pangan Jajanan Anak Sekolah di Jakarta - Martha Uli Intan Sari Sinaga; Winiati Puji Rahayu; Yanti Kamayanti Latifa (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2020)
School snack food (SSF) needs to be a priority of food safety guarantees because the consumption of SSF concerns the quality of the young generation. The method of delivering information on SSF safety is an effective way to increase awareness of food safety. This study aimed to explore the preferences of high school students for the search for food safety information. The survey was conducted to 100 SMA and MA students in DKI Jakarta; the results were processed by SPSS program using chi-square analysis. The survey results showed that 60% of students liked information from online media. Fifty percent of respondents considered the source of information as the primary consideration, and 46% believed the government was a trusted source. SMA students prioritized information sources, while MA students prioritized sources and the title of information, which were positively correlated (p<0.05) with the infographic elements. Female students liked social networking and trusted the government and family. The male students preferred online media and trusted the government, family, and peers who are positively correlated with the type of media and trusted parties. The higher the level of parent’s education, the more knowledge about the development of information technology which is positively correlated with the choice of media types for students.